THE SIZE PROFILE OF EXTERNAL URETHRAL ORIFICIUM IN MALE ADULT - Susanto, Gaeta Nurprimavera; Danarto, Raden; Ali, Zulfikar (Indonesian Urological Association, 2019)
Objective: External urethral orificium (EUO) is the outermost part of the urethra. It lies on the outside, then the operation tool for endourology transurethra must pass urethra meatus externus first before they can go deeper. Unfortunately there is no study addresses the size of EUO of male adults in Indonesia. This study was aimed to know the size of the EUO in males adult. Material & Methods: This study was a prospective study by taking the primary data in the Sardjito General Hospital and Kardinah General Hospital, Tegal and implemented during the period from October to December 2016. There were 50 samples of males adult. The exclusion criteria in this study were male patients with meatal stenosis or patients with a history of surgery on the penis or instrumentation of the urethra. External urethra orifice size measurements performed with a digital caliper, and then converted to scale the size of Fr. The data were then analyzed by Npar test with the Kolmogorov-Smirnov test, and then T-test with linear regression. Results: There were 50 adult male patients with a mean age of 52.54 ± 10.34 years. For sizes vary with the size of 16.5-26.4 Fr. From the analysis of the size of the EUO obtained a mean size of 22.72 ± 2.62 for Indonesian adult male. Conclusion: The average size of the adult male EUO was 22.72 ± 2.62 Fr.